MATHEMATICS EDUCATION IN SINGAPORE - AN INSIDER'S PERSPECTIVE - Berinderjeet Kaur (Journal on Mathematics Education, 2014)
Singapore's Education System has evolved over time and so has Mathematics Education in Singapore. The present day School Mathematics Curricula can best be described as one that caters for the needs of every child in school. It is based on a framework that has mathematical problem solving as its primary focus. The developments from 1946 to 2012 that have shaped the present School Mathematics Curricula in Singapore are direct consequences of developments in the Education System of Singapore during the same period. The curriculum, teachers, leaners and the learning environment may be said to contribute towards Singapore's performance in international benchmark studies such as TIMSS and PISA.Keywords: Mathematics Education, Singapore, Differentiated Curriculum, TIMSS, PISA